2012
DOI: 10.1136/bmjopen-2012-002094
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions and behaviours related to the risk of infection with Aedes mosquito-borne diseases: a cross-sectional study in Southeastern France

Abstract: ObjectivesTo explore public perceptions and behaviours related to the risk of flavivirus and alphavirus infection in Southeastern regions of France following the recent colonisation of the Asian tiger mosquito, Aedes albopictus, and the identification of four autochthonous cases of dengue and chikungunya fever in these regions.DesignCross-sectional telephone survey using a proportional random digit dialling selection method.SettingInterviews were conducted from 28 November 2011 to 29 January 2012 using a compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 28 publications
(8 reference statements)
0
41
1
Order By: Relevance
“…These factors should be further reviewed and considered in the development and implementation of future large-scale mosquito-borne disease prevention programs. In previously conducted infectious disease studies, these social and cognitive factors have consistently been found to influence the engagement in health protective behaviors [35,42,43]. However, in our study, only a few cognitive factors were associated with the protective health behaviors recommended by the public health authorities at the early stage of the epidemic.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…These factors should be further reviewed and considered in the development and implementation of future large-scale mosquito-borne disease prevention programs. In previously conducted infectious disease studies, these social and cognitive factors have consistently been found to influence the engagement in health protective behaviors [35,42,43]. However, in our study, only a few cognitive factors were associated with the protective health behaviors recommended by the public health authorities at the early stage of the epidemic.…”
Section: Discussioncontrasting
confidence: 51%
“…This result is somewhat unexpected since the perceived exposure to vectors (seeing bugs, being bitten) has been repeatedly found as one of the most important triggers for taking health protective actions [35,36]. This cannot be explained by an important perceived lack of behavioral control because this variable was not found to be associated with the adoption of preventive measures against mosquitoes.…”
Section: Discussionmentioning
confidence: 85%
“…The presence of containers plays an important role in the density of Aedes larvae, as the more containers present will make more crowded mosquito density and will become more populous of Aedes mosquitoes (Raude, 2012). The more densely populated the Aedes mosquitoes, the higher the risk of dengue virus infection with faster spreading time therefore resulting in the number of cases of dengue fever to rapidly increase which eventually resulted in the outbreak of dengue disease (Sitio, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…This is the first study on the perception of the present and future risk of vector-borne diseases (i.e., dengue, [33][34][35][36], H1N1pdm flu [37][38][39] and H5N1 avian flu [40][41][42]; others have focused on general practitioners in France [43][44][45], both general population and practitioners [46], French pharmacists [47] or risk perception in Europe and other countries worldwide [48][49][50]. The appearance of various emerging infectious diseases during the last two decades (e.g., chikungunya, SARS-CoV, MERS-CoV, Ebola virus, Zika), as well as that of antibiotic-resistant bacteria, has stimulated research on risk perception in the general public and policy-makers [51][52][53][54][55].…”
Section: No Studies On the Arboviral Disease Risk Perception By Healtmentioning
confidence: 99%
“…Moreover, the French medical and research communities have rapidly developed interdisciplinary programs to better understand and fight these new diseases, for instance the Research and ACTion targeting emerging infectious diseases (REACTing) [25]. From 2009 to 2016, the general French population's awareness of these arboviral risks has strongly changed; from a low awareness among the population [26], citizen views of potential risks has increased during this period with some heterogeneities observed depending on the region and mosquitoe settlement [27]. Meanwhile, French national health authorities have continuously pursued information campaigns on the potential risks of transmission of these three arboviral infections.…”
Section: Introductionmentioning
confidence: 99%